Dream factories of a former colony : American fantasies, Philippine cinema - Capino, José B. (University of Minnesota Press, 2010)
Philippine cinema, the dream factory of the former U.S. colony, teems with American figures and plots. Local movies feature GIs seeking Filipina brides, cold war spies hunting down native warlords, and American-born Filipinos wandering in the parental homeland. The American landscape furnishes the settings for the triumphs and tragedies of Filipino nurses, GI babies, and migrant workers. By tracking American fantasies in Philippine movies from the postindependence period to the present, José B. Capino offers an innovative account of cinema's cultural work in decolonization and globalization. C.